FRUIT FLIES (DIPTERA: TEPHRITIDAE) DIVERSITY IN HORTICULTURAL FARM OF MERAWANG SUB-DISTRICT, BANGKA DISTRICT, BANGKA BELITUNG ISLANDS - Supratiwi, Rahayu; Apriyadi, Rion; Asriani, Euis (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2020)
Fruit flies (Diptera: Tephritidae) are main pests in fruit and vegetable cultivation. There are 4000 species offruit flies in the world and 35% of them are important pests, including commercial fruits that have high economic value.Merawang District is one of the centers of horticultural production, especially fruits and vegetables. One of the threats to theproduction of horticultural commodities is the attack of fruit flies. The purpose of this study was to determine the diversity,distribution, and types of fruit flies in horticultural crops in Merawang Sub-District, Bangka District. The research wasconducted in descriptive method, in this case, the survey method was also used. The sampling was done in purposivesampling method. In total, 1248 specimen of fruit flies were collected by using different attractant traps and identified. Themethyl eugenol (ME) and cue lure (CUE) attractants trapped 1076 and 172 specimens, respectively. The diversity of fruit fliesin Merawang Sub-District was relatively low, in total 9 species fruit flies were observed and identified as Bactrocera dorsalis(Hendel), B. umbrosa (Fabricius),Ã‚Â  B. carambolae (Drew & Hancock), B. occipitalis (Bezzi), Zeugodacus cucurbitae (Coquillett),B. albistrigata (de Meijer), Z. caudata (Fabricius), B. limbifera (Bezzi), and Dacus nanggalae (Drew & Hancock). The speciesdominant observed at the study site were B. dorsalis (Hendel), B. carambolae (Drew & Hancock), and B. occipitalis (Bezzi).Air Anyir Village was the highest number of fruit flies species.